THEORETICAL FOUNDATIONS OF STUDYING THE FORMATION OF CHARACTER TRAITS IN SCHOOLCHILDREN - Tojiddin Zayniddinov (Web of Journals Publishing, 2025)
This article includes questions about the correct use of human psychological capabilities and their implementation, and on the basis of this, assign plans for the future. This is considered the main task of every state and every nation. Each person must realize that they are part of the community and the people.
Keywords: Struggle, students, psychological diagnosis, psychological development, components, pedagogical experience.